Case Report: Undifferentiated embryonic sarcoma of an adult liver - Li, Shengyong; Bao, Lexin; Li, Xiujun; Bai, Liang (Frontiers in Oncology, 2025)
Undifferentiated embryonal sarcoma of the liver is a malignant mesenchymal tumor of the liver that predominantly affects children, with exceedingly rare occurrence in adults, and is associated with a poor prognosis. We present a case of undifferentiated embryonal sarcoma of the liver in a previously healthy 45-year-old man admitted to our hospital due to fever. Magnetic resonance imaging revealed a cystic-solid mass in the right lobe of the liver, measuring approximately 15 * 13 * 13 cm in size. Imaging diagnosis raised a suspicion of biliary cystadenocarcinoma with hemorrhage. A hepatic resection was successfully performed, and the histologic diagnosis was undifferentiated embryonal sarcoma of the liver. The patient received a chemotherapy regimen of ifosfamide combined with epirubicin after surgery, and no recurrence was observed after 6 months of follow-up. We herein review the clinical, radiologic, and pathologic features of this rare tumor.